Goat Meat Production and Quality - Mahgoub, O (CABI, 2014)
Goat Meat Production and Quality consists of 15 chapters and was compiled with the aim of providing information on basic as well as more advanced aspects of goat meat science to the wide range of scientists and professionals concerned with goat meat research and edu- cation. It is also intended to serve as a textbook for university and college students on meat production from ruminant animals. The goat industry, which has been lagging behind other livestock industries such as cattle, sheep and pigs, would also benefit from this book. Goat Meat Production and Quality has been meticulously written by internationally recog- nized experts and includes the most recent advances in goat meat science. The contributing authors hail from various parts of the world including Africa, Asia, North and South Amer- ica, Australia and Europe. The goat was one of the earliest animals to be domesticated. Over many centuries, goats have served human communities around the world to provide food, fibre and other products such as leather and manure. For decades, the goat has been regarded as a major cause of environmental destruction by overgrazing leading to desertifi- cation. However, more recently, there has been growing recognition of the goat as an ani- mal that provides sustainable livelihoods for many people, especially in the most deprived regions of the world. Goats provide valuable animal protein at a very low cost by utilizing marginal land usually rejected by other livestock to support low-income people in Asia, Africa and other underdeveloped parts of the world. In Europe, particularly southern Euro- pean countries, the goat has been used commercially for milk production and cheese mak- ing, while goat kids serve as a by-product for meat production.